2000
DOI: 10.3168/jds.s0022-0302(00)74939-3
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Exchange by the Mammary Gland of Lactating Goats when Histidine Limits Milk Production

Abstract: The aim of this study was to monitor amino acid (AA) exchange kinetics of the mammary gland in response to an imposed limitation on His supply for milk production. Lactating goats (n = 4, approximately 120 DIM) were fed a low protein ration that provided only 77% of metabolizable protein and 100% of energy requirements for milk production. The protein deficiency was alleviated by infusion into the abomasum of an AA mixture (67 g/d) including (+H; 4.4 g/d) or excluding (-H) His. Goats were assigned to treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 24 publications
9
106
0
Order By: Relevance
“…The present results also show that the arterial limitation in methionine did not affect mammary blood flow as observed when histidine severely limited milk protein synthesis [6]. Such mammary arterial blood flow adjustment has also been observed when methionine was limiting milk protein synthesis [22].…”
Section: Mammary Metabolismsupporting
confidence: 64%
See 2 more Smart Citations
“…The present results also show that the arterial limitation in methionine did not affect mammary blood flow as observed when histidine severely limited milk protein synthesis [6]. Such mammary arterial blood flow adjustment has also been observed when methionine was limiting milk protein synthesis [22].…”
Section: Mammary Metabolismsupporting
confidence: 64%
“…This contrasts with observations made from the comparison of separate experiments, which used cows at similar lactation status and similar protein deficient diets. These results suggest that milk protein yield in response to additional essential amino acid supply would be greater with jugular than 6 results in a modification in milk yield without any alteration in milk protein concentration.…”
Section: Animal Performancesmentioning
confidence: 77%
See 1 more Smart Citation
“…Subtraction of 30 g d -1 His caused a decrease of 186 g d -1 in protein yield and an increase of 181 g d -1 in fat yield. Bequette et al (2000) induced very low circulating concentrations of His in lactating goats by subtracting approximately 40% of the His from the total duodenal supply. Mammary blood flow rate was 36% higher at 8 µM plasma His compared to 73 µM.…”
Section: Subtraction Experimentsmentioning
confidence: 99%
“…Correction of a His deficiency has repeatedly been shown in subtraction experiments to increase milk and milk protein yields and decrease milk fat yield (Fraser et al 1991;Kim et al 1999;Bequette et al 2000;Weekes and Cant 2000;Cant et al 2001). In early-lactation cows fed a 9%-protein diet plus 1.2 kg d -1 abomasal AA, Weekes and Cant (2000) found that improvements in each of Met, Lys and His supplies caused protein yields to increase, while fat yields dropped, but the effect was most pronounced for His.…”
Section: Subtraction Experimentsmentioning
confidence: 99%